Desecrated archives: forms of performance in Mi Vida Después (2009) and Antígona Oriental (2012) - Morales, Noelia (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2024)
In this paper we will focus on the plays Mi vida después (2009) by the Argentine artist Lola Arias and Antígona Oriental (2012) by the Uruguayan playwright Marianella Morena. To do this, we will take as one of the possible axes of analysis, the comparative study of archives and their links with the forms of performance based on the concept of desecration by Giorgio Agamben (2013) and the reappropriation carried out by Lía Noguera (2019) in the field of arts.